SHARIA STARTUP DEVELOPMENT MODEL THROUGH BUSINESS INCUBATORS - Chandra Utama, Ramadhonni; Zaerofi, Afif; Mukhlis Yusuf, Achmad (Universitas Ibn Khaldun Bogor, 2023)
Startups have an important role in economic development, but they also have a high failure rate. A business incubator is an institution that aims to help startups with services and resources to facilitate their development. However, currently there is no business incubator that specifically specializes in developing sharia startups. This study has objectives to (1) describe the structure of the incubation model in the current business incubator, (2) identify the needs of startups in developing their business from the sharia side and (3) propose the development of an incubation model for the right business incubator for sharia startups. Methods of data analysis in this research using a qualitative study where business incubators and sharia startups are interviewed about the incubation process model and the business needs of sharia startups. The results of this study are (1) the three incubation models of the three business incubators consist of a process that is divided into 3 stages, namely pre-incubation, incubation, and post-incubation, but the three business models are not suitable for developing a sharia startup business. Startups hope to participate in a business incubation program that supports their business in terms of sharia. (2) The results of research on startup needs in developing their business found that 50% of startups need knowledge of sharia muamalah fiqh knowledge principles, 25% of startups need digital branding training according to sharia, 50% of startups need networking and mentoring with mentors who have experience and expertise in the field. sharia sector and the most dominant is 75% startups need access to sharia business funding. (3) Therefore, the results of the last study, the researchers developed an incubation model based on the needs of sharia startups which have differences in the general/conventional incubation model, namely the addition of sharia-based activities at each stage. In the pre-incubation stage, namely the selection process for sharia-based startups, introduction to sharia economics and sharia digital training capabilities. In the incubation stage, namely knowledge of sharia muamalah fiqh, networking and mentoring with mentors who have experience and expertise in the field of sharia and character training of Muslim entrepreneurs. In the post-incubation stage, namely access to sharia business funding and a network of Muslim entrepreneurs.